Early detection of left ventricular dysfunction in patients with end-stage renal disease on hemodialysis by speckle-tracking echocardiography - Saud Mohamed; Abdelaziz O. Mohamed; Mohamed G. Alsaady; Hala A. Mahmoud (Heart India)
Background: In individuals with end-stage renal disease (ESRD) cardiovascular imaging modalities show a high prevalence of left ventricular hypertrophy (LVH), systolic/diastolic dysfunction and ventricular dilatation (dilated cardiomyopathy), which are strongly linked to a poor prognosis. Aim: The aim of the present study was the early detection of left ventricle dysfunction in ESRD patients on hemodialysis (HD) using speckle-tracking imaging. Subjects and Methods: This was a cross-sectional study performed on 199 patients with ESRD that referred to HD unit in Aswan University Hospital. All patients underwent echocardiographic evaluation by traditional transthoracic 2D echocardiography, tissue Doppler imaging, and speckle tracking. Results: Global longitudinal strain was significantly lower in diabetic ESRD patients and in ESRD patients with LVH than nondiabetics and those without LVH (P < 0.05). Conclusion: Speckle-tracking echocardiography can early detect the left ventricle dysfunction in ESRD patients on HD, and global longitudinal strain is the most sensitive echocardiographic parameter to predict systolic dysfunction.